Produção de mudas de maracujazeiro-amarelo por enxertia Hipocotiledonar sobre sete espécies de passifloras - Filho, Geraldo Costa Nogueira; Roncatto, Givanildo; Ruggiero, Carlos [UNESP]; de Oliveira, João Carlos [UNESP]; Euclides, Braga Malheiros [UNESP] (FapUNIFESP (SciELO), 2011)
The yellow passion fruit (Passiflora edulis Sims f. flavicarpa Deg.) Passifloraceae is the main crop in Brazil, and the crop has found some difficulties, particularly concerned to the orchards longevity, which has been reduced due to diseases and nematodes that attack the root system. This study was carried out to establish technologies for the production of seedlings of yellow passion fruit by hypocotyledonary grafting on seven rootstocks. The treatments used as rootstocks were: P. edulis f. flavicarpa, P. caerulea, P. alata, P. giberti, P. coccinea, P. cincinnata and P. setacea. The experimental design was completely randomized, with 36 replications for each rootstock. The percentage of graft survival, plant height, number of leaves and rootstock diameter were the characteristics evaluated. The hypocotyledonary grafting methodology was successful for most species tested. P. caerulea, P. giberti, P. cincinnata and P. flavicarpa were the stood out rootstocks by their high conditions of plants growth, and by their early plants production.
Seedling production of yellow passion fruit by Hypocotyledonary grafting on seven species on passifloras
Keywords: Compatibility; Methodology; Micrografting; Passiflora spp.; Table grafting; Vegetative propagation